Mengembangkan Kemampuan Berbahasa Pada Anak Usia 5-6 Tahun Menggunakan Metode Bernyanyi di Desa Panca Tunggal - Siti Nadirah; Holijah Holijah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This community service program in the form of service is based on collaboration between Real Work Lecture students at the Raden Fatah State Islamic University, Palembang, with Panca Tunggal Village, sungai Lilin District, Musi Banyuasin Regency, South Sumatra Province to observe the development of early childhood in the Panca Tunggal village community, The aim of this activity is to improve children’s development and provide outreach to the community, especially parents, regarding the impact of developing language skills in early childhood. The method used is a qualitative method which uses data triangulation assessment techniques. Developing language skills among young children has positive and negative impacts on children, one of which can affect children’s language development. Speaking with friends whitout parental supervision can cause children to speak bad language such as dirty language. In Panca Tunggal Village there are several children who do not know the impotance of good and correct language which results in children speaking carelessly and foul language